Cultural and linguistic adaptation among Japanese women migrants in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Modern Languages at Massey University - Natusch, Barry Antony (Massey University, 1986)
A survey af the cultural and linguistic adaptation of 76 married Japanese women in New Zealand was carried out by means of interviews and language tests. Two basic sub-groups were identified: those who were married to Japanese husbands (INTRA subjects) and those who were interculturally married (INTER subjects). A number of marked differences, in particular those related to age and marriage type, were observed to exist between these INTRA and INTER groups. The INTER subjects appeared to have made a smoother cultural adaptation to life in New Zealand than those in the INTRA group. The INTRA subjects all identified themselves culturally as Japanese as did the more recently arrived INTER subjects. However, some of the INTER group who had lived in New Zealand for many years appeared to have a cultural identity which was neither fully Japanese nor western. The migrants continued to maintain the Japanese language for communicating among themselves although it did not seem to be passed on to the children of the INTER subjects. A considerable shift from Japanese to English was observed among the INTER subjects but was less evident among subjects in the INTRA group. Levels of oral proficiency in English were not particularly high among the subjects, ranging between 0+ and 3+ on the Foreign Service Institute (FSI) assessment scale. Most of the INTRA group were assessed between level 0+ and 1+ on the scale whereas the majority of INTER subjects scored between levels 2 and 3+. This difference in oral proficiency was due mainly to influences associated with intercultural marriage. An analysis of the subjects' oral English revealed that the INTRA subjects had higher frequencies of error in their English than the INTER subjects. Many phonological errors appeared to be due to interference from Japanese. An analysis of grammatical errors involving noun morphology, verb morphology and article usage, however, suggested several possible causes of error including interference, oversimplification, the learners' false hypotheses, faulty instruction and idiosyncratic variation. The nature and frequency of these errors resulted in pidginlike characteristics being observed in the subjects' English. Lexical errors and communication strategies employed by the subjects were also described.
Keywords: Japanese women in New Zealand; Acculturation; Cultural identity; Japanese migrants; English proficiency; Japanese speakers of English